Is wearing high heels a female mating strategy? Revisiting the original study using qualitative methods - Masaryk, Radomír; Synak, Nikola; Belišová, Michaela (Frontiers in Psychology, 2022)
The 2020 study entitled ‘Wearing high heels as female mating strategy’ by Pavol Prokop and Jana Švancárová claimed that when females imagined an interaction with an attractive male, their preference for high heels steeply increased, compared with an imagined interaction with an unattractive male. The authors concluded that wearing high heels seem to be a form of sexual signaling by females in intersexual interactions. The present paper revisits this study through a psychological standpoint, rather than a biological one. In addition to proposing hypothetical dating scenarios, as in the original study, we also asked participants about how they went about getting ready to go on a date, the significance of dating to them, and their thinking behind choosing particular outfits for a date. We conducted ten focus groups (N = 50), recruiting from a similar sample of participants to those in the original study. For our study we followed principles of Thematic Analysis to identify the key themes in the narratives related to dating and beautification. We also used the photo elicitation methodology to observe what footwear our participants own. Our data interpretation from these two sources suggests that young women tend to see dates as social events not necessarily leading to sex; that they do not regard high heel shoes as a means of beautification; and that they take account of practical considerations when getting dressed up for a date. Moreover, young women tend to use beautification with caution. We conclude that the relationship between the tendency to use beautification and attractiveness of a potential partner is far from straightforward; and relying on binary responses to hypothetical scenarios does not provide convincing evidence.